Fatigue Risk of Long-Distance Driver as the Impact of the Duration of Work - Zuraida, Rida (Bina Nusantara University, 2015)
Studies on the driver's fatigue, must focus on at least two things: the time-of-day that affect by circadian factors, and time-on-task. This paper discusses the risk level of driver fatigue, which generally have to drive in a long duration or more than 4 hours. The risk of fatigue was assessed using Fatigue Likelihood Scoring (FLS) by Transport Canada. Based on interviews with 24 inter-city bus drivers, 18 of the 24 drivers have a very high risk of fatigue that characterized by FLS scores greater than 20, while the rest have a high risk driver that characterized by FLS value greater than 10. A high risk of chronic fatigue that experienced by most of drivers caused by working hours which is more than 36 hours in a week, the duration of the shift of greater than 8 hours a day, lack of time off, the amount hours of driving at night, and the amount of time off.